Pneumonia in a patient with lung cancer - SANTOS, Vitorino Modesto dos; SANTOS, Lister Arruda Modesto dos (Revista de Ciências Médicas, 2017)
The aim of the present report is to alert health care workers about a 64–year–old patient diagnosed with adenocarcinoma in the right lung treated with pemetrexed disodium, cisplatin and dexamethasone. He evolved with prolonged neutropenia, symptoms of lower airways infection, and recent pulmonary infiltrate in the radiographic image. The cultures for bacteria and mycobacteria in the blood and sputum were negative. Because of the lack of response to treatment with broad spectrum antibiotics and maintenance of neutropenia, a transbronchial biopsy was performed, which demonstrated infection by Aspergillus fumigatus. The patient was treated.